2012
DOI: 10.5483/bmbrep.2012.45.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of Camellia japonica oil

Abstract: Camellia japonica oil (CJ oil) has been used traditionally in EastAsia to nourish and soothe the skin as well as help restore the elasticity of skin. CJ oil has also been used on all types of bleeding instances. However, little is known about its anti-inflammatory effects. Therefore, the anti-inflammatory effects of CJ oil and its mechanisms of action were investigated. CJ oil inhibited LPS-induced production of NO, PGE2, and TNF-α in RAW264.7 cells. In addition, expression of COX-2 and iNOS genes was reduced.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 34 publications
0
23
0
4
Order By: Relevance
“…20,55 Monokine induced by INF-c expression is significantly decreased after topical application of anti-inflammatory substances, such as 5-aminoimidazole-4-carboxamide-1-b-d-ribofuranoside and adiponectin. 34,46 We suspect that inhibition of the NF-jB signaling pathway by the CJ extracts, as proven by Kim S et al 2 led to the decreased expression of anti-inflammatory cytokines and chemokines observed in this work.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…20,55 Monokine induced by INF-c expression is significantly decreased after topical application of anti-inflammatory substances, such as 5-aminoimidazole-4-carboxamide-1-b-d-ribofuranoside and adiponectin. 34,46 We suspect that inhibition of the NF-jB signaling pathway by the CJ extracts, as proven by Kim S et al 2 led to the decreased expression of anti-inflammatory cytokines and chemokines observed in this work.…”
Section: Discussionmentioning
confidence: 62%
“…2 The anti-inflammatory action of CJ extracts also was shown in this study. Western blot analysis performed during the in vitro study demonstrated that CJ extracts exert antiinflammatory effects by decreasing the expression of COX-2 The expression of COX-2 is upregulated in the ocular surface after injury and during inflammation.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Since nitric oxide (NO) is one of the inflammatory mediators, inflammation is characterized by the secretion of NO, and modulation of NO is considered a possible treatment for inflammatory disease (3). The increase in inducible nitric oxide synthase (iNOS) and cyclooxygenase (COX)-2 causes cell damage following the increased production of NO and prostaglandins (PGs) (4). Suppressing the induction of COX-2 is a new strategy in the prevention of inflammation and COX-2 expression is also related to the activities of many intracellular signaling proteins, such as extracellular signal-regulated kinase (ERK), mitogen-activated protein kinase (MAPK), and Jun-N terminal kinase (JNK) (5).…”
Section: Introductionmentioning
confidence: 99%
“…NO is generated through nitric oxide synthases enzyme (iNOS), while PGE 2 is produced by cyclooxygenase-2 enzyme (COX-2) (9). The expression of iNOS and COX-2 are regulated via mitogen activated protein kinase (MAPK) signaling pathways (10-12).…”
Section: Introductionmentioning
confidence: 99%